An Overview of Knut Hamsun’s Reception in the Romanian Cultural Printed Press: 1902–1989 - Lăţug, Diana (Nordlit, 2016)
This paper outlines major directions in the reception of Knut Hamsun in the Romanian cultural printed press. The research is based on a plethora of articles in Romanian cultural periodicals spanning the years 1902–1989. The results shall be encompassed in a doctoral thesis on the same subject. The structure of the paper follows a chronological overview of the phases of his reception. Because the interwar period has been discussed in detail in other previous papers, focus shall be put on the communist era. The first oscillations occur between the years 1940–1947. As a result of the Stalinist regime, Hamsun is only portrayed in terms of his political views. Communism thus reduces his authorship to a minimum. A renewed interest emerges in the 1980s through a new series of translations and articles. This interest is then compounded with the founding of the Department of Scandinavian Languages and Literatures in Cluj in 1991 and continues to the present. Articles from all of these time periods are evaluated both quantitatively and qualitatively to acquire a holistic image of how Hamsun is received by Romanian culture.